Subsídios técnicos e conceituais para implantação de pagamento por serviços ambientais em Caxias do Sul - RS - Velho, Janaina Ribeiro (My University, 2022)
In recent years, Brazilian municipalities have been challenged from the point of view of governance, especially with the attribution of goals involving the theme of environmental sanitation and water security. Although the municipality of Caxias do Sul has a Municipal Basic Sanitation Plan and the Water Zone Law (ZA) - which regulates land use, subdivision of land and respiratory activities in these areas, the targets immune from the Marco Legal do Sanitation are of great importance. Even with the legal regulations in areas producing water for public supply, its non-compliance and the verification of environmental damage are noticeable. However, most environmental legislation has a punitive nature, within the legal basis of command and control. One possibility to minimize this situation is to promote incentives to people who voluntarily protect natural resources, through the protective principle received and the Payment for Environmental Services (PES). In the meantime, the general objective of the study is the technical and conceptual supervisors for the implementation of PES in rural basins in the municipality of Caxias do Sul. In order to achieve the specific objectives, an extensive bibliographical research and documental analysis was carried out. The results obtained refer to: the guarantee of legal requirements related especially to water resources and PSA; the technical requirements related to the PSA; and the characterization of catchment basins and water reserves. In the latter, the characterization of the basins as a management and planning unit and the socio-environmental analysis of the rural ZA based on technical information from the municipal sanitation authority stand out, in order to meet specific prerequisites of the Water Producer program coordinated by National Water and Basic Sanitation Agency. The objectives were satisfactorily met, especially with the elaboration of the summary table of the main technical information. It is recommended that the autarchy expand its studies, testing a more detailed technical, economic and environmental analysis within the results obtained in this research, which will culminate in the answer if the municipality of Caxias do Sul can be effectively subordinated to the selection process of the Producer Program of water. [resumo fornecido pelo autor]
Nos últimos anos, os municípios brasileiros estão sendo desafiados sob o ponto de vista de governança, especialmente, com a imputação de metas que envolvem a temática de saneamento ambiental e segurança hídrica. Apesar do município de Caxias do Sul possuir Plano Municipal de Saneamento Básico e a Lei de Zona das Águas (ZA) - que regulamenta o uso do solo, o parcelamento do solo e as atividades econômicas nestas áreas, as metas estabelecidas pelo Marco Legal do Saneamento são de grande vulto. Mesmo com os regramentos legais em áreas produtoras de água para o abastecimento público, é perceptível seu descumprimento e a verificação de danos ambientais. Entretanto, a maioria das legislações ambientais possuem o cunho punitivo, dentro do fundamento jurídico de comando e controle. Uma possibilidade de minimizar esta situação é promover incentivos às pessoas que protegem voluntariamente os recursos naturais, por meio do princípio protetor recebedor e do Pagamento por Serviços Ambientais (PSA). Neste ínterim, o objetivo geral do estudo é analisar os subsídios técnicos e conceituais para implantação de PSA em bacias rurais no município de Caxias do Sul. Para alcançar os objetivos específicos foi realizada uma ampla pesquisa bibliográfica e análise documental. Os resultados obtidos referem-se: à determinação de requisitos legais relacionados especialmente aos recursos hídricos e ao PSA; aos requisitos técnicos relacionados ao PSA; e a caracterização das bacias de captação e reservas hídricas. Neste último, destaca-se a caracterização das bacias como unidade de gestão e planejamento e a análise socioambiental das ZA rurais baseada em informações técnicas advindas da autarquia municipal de saneamento, a fim de atender a pré-requisitos específicos do programa Produtor de Águas coordenado pela Agência Nacional de Águas e Saneamento Básico. Os objetivos foram satisfatoriamente atendidos, especialmente com a elaboração do quadro resumo das principais informações técnicas. Recomenda-se que a autarquia amplie seus estudos, ensejando em uma análise técnica, econômica e ambiental mais detalhada dentro dos resultados obtidos nessa pesquisa, o qual culminará na resposta se o município de Caxias do Sul pode ser efetivamente submetido ao processo seletivo do Programa Produtor de Água. [resumo fornecido pelo autor]
Keywords: Engenharia ambiental; Recursos hídricos - Caxias do Sul (RS) - Aspectos ambientais; Encargos tributários sobre o impacto ambiental - Caxias do Sul (RS); Direito ambiental - Brasil; Bacias hidrográficas; Environmental engineering; Water resources - Caxias do Sul (Brazil) - Environmental aspects; Environmental impact charges - Caxias do Sul (Brazil); Environmental law - Brazil; Watersheds